THE INFLUENCE OF BRAND IMAGE AND CUSTOMER PERCEIVED VALUE TO CUSTOMER SATISFACTION AND REVISIT INTENTION IN ECO GREEN PARK, BATU, EAST JAVA - Thomas Tunggul Pudiprabowo; Ananda Sabil Hussein (Jurnal Ilmiah Mahasiswa FEB, 2014)
The purpose of this study is to measure the influence of brand image and consumer perceived value on customer satisfaction and revisit intention in Eco Green Park, Batu, East Java. The use of variables is able to solve problems that arise in Eco Green Park. The sample in this research is the consumer who has ever visited the Eco Green Park, Batu, East Java. Convenience sampling technique using sampling with 150 respondents. Partial Least Square (PLS) analysis is applied to analyze the data using the model outer and inner models. The results showed that brand image has a significant relationship to customer satisfaction and intentions to come back, while the consumer perceived value also has a significant influence on consumer satisfaction and revisit intention. Consumer satisfaction itself has a significant influence on the revisit intention.   Keywords: brand image, perceived value, customer satisfaction, revisit Intention, Eco Green Park.